CsPbBr3-based photoanode prepared by single-step Chemical vapor deposition of tunable thickness perovskite films - Sosa Costa, José Raul; Fernández Izquierdo, Leunam; del Río, Rodrigo; Navarrete-Astorga, Elena; Leinen, Dietmar; Hevia Zamora, Samuel Alejandro (Elsevier, 2024)
Cesium Lead Bromide (CsPbBr3) perovskite films have gained significant attention in photoelectrochemistry due to their promising properties. However, their widespread application necessitates scalable processing methods to produce high-quality films. Current techniques often involve post-synthesis steps to achieve desirable crystalline films or surface coverage for optimal performance. This research performed a single-step Chemical Vapor Deposition (CVD) approach to grow high-quality CsPbBr3 films. This methodology offers precise control over film thickness and grain orientation, crucial for optimizing photoelectrochemical response. The procedure simplifies fabrication by bypassing annealing or toxic solvent excess and growing films directly from CsPbBr3 crystals. Film thickness was controlled by adjusting growth time and precursor mass parameters to examine the photoelectrochemical performance across thicknesses ranging from 0.6 µm to 2.5 µm. Optimal results were achieved with dense, compact films 1.5 µm thick, which exhibited oriented grains along the (121) plane. Optical, structural, and morphological analyses confirmed a predominantly pure orthorhombic phase, although slight impurities were noted in thinner films. The 1.5 µm films showed a four-hour stable photocurrent of 6.2 mA/cm² at 1.23 V versus reversible hydrogen electrode (RHE) under simulated solar conditions, underscoring their potential in advancing perovskite-based electrodes for efficient photoelectrochemical solar fuel generation.
https://openpolicyfinder.jisc.ac.uk/id/publication/11418
Keywords: Deposición química de vapores; Perovskite; Single-step chemical vapor deposition; Photoanode; Water splitting